Echolocation calls of Natalus primus (Chiroptera: Natalidae): Implications for conservation monitoring of this species. Issue 1 (1st January 2017) - Sanchez, Lida; Moreno, Christian R.; Mora, Emanuel C.
Abstract: Natalus primus constitutes one of the most vulnerable mammalian species of Cuba. Until now, only one extant population is known to live in one single cave in the westernmost part of Cuba, within the Guanahacabibes National Park. Over multiple trips, we recorded ultrasonic vocalizations from several individuals of this species. We found short, high frequency-modulated multiharmonic calls for N. primus ; these could be used to identify this species in acoustic inventories conducted in Cuba. Identifying N. primus through their echolocation calls will allow conducting passive acoustic monitoring, constituting a noninvasive approach to study this vulnerable species without causing disturbances on its roosts and foraging areas.